Nickel-based alloy powder for additive manufacturing and preparation method thereof

The nano-scale tungsten carbide in nickel-based alloy powder is uniformly mixed by magnetic stirring, which solves the problems of pores and cracks in the additive parts, and significantly improves the mechanical properties and usage performance of the additive parts.

CN114769579BActive Publication Date: 2025-02-25JIANGSU UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210491292.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-07
Publication Date
2025-02-25
Estimated Expiration
2042-05-07

AI Technical Summary

Technical Problem

The prior art is difficult to uniformly mix the nano-scale hard phases in nickel-based alloy powders in laser deposition additive manufacturing, resulting in common defects such as pores and cracks in additive parts, affecting their mechanical properties and usage properties.

Method used

The magnetic stirring method was used to mix 60-80 parts by weight of spherical Ni60 powder with a particle size of 70-120 microns and 40-20 parts by weight of tungsten carbide with a particle size of 20-100 nanometers, and the nano-WC and Ni60 surfaces were formed by magnetic stirring. Core-shell structure reduces the agglomeration of the hard phase and further purifies the alloy powder during the drying process.

Benefits of technology

The uniform mixing of nickel-based alloy powder is achieved, which reduces pores and cracks in the additive parts, significantly improves the wear resistance, corrosion resistance and mechanical properties of the additive parts, and simplifies process operations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114769579B_ABST
    Figure CN114769579B_ABST
Patent Text Reader

Abstract

The invention discloses a nickel-based alloy powder for additive manufacturing and a preparation method thereof, belonging to the technical field of additive manufacturing powder preparation. The alloy powder comprises 60-80 parts by weight of spherical Ni60 powder with a particle size of 70-120 microns and 40-20 parts by weight of tungsten carbide with a particle size of 20-100 nanometers. The nickel-based alloy powder for additive manufacturing of the invention is mixed using magnetic stirring, and the obtained powder can improve the relevant properties of laser deposited additive parts, reduce the occurrence of pores and cracks in the coating, and has a wide range of applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a nickel-based alloy powder for additive manufacturing and a preparation method thereof, belonging to the technical field of additive manufacturing powder preparation. Background Art

[0002] Laser deposition additive manufacturing utilizes the basic principles of rapid prototyping, uses metal powder as raw material, and adopts a high-energy-density laser beam as the energy source. According to a predetermined processing path, the metal powder fed synchronously is melted layer by layer, rapidly solidified, and deposited layer by layer, thereby realizing the direct manufacturing of metal parts.

[0003] Cracking of laser-deposited additive parts is an important factor that hinders the widespread application of metal additive technology in industry. Since laser deposition additive manufacturing technology is a rapid heating and cooling process, there is a large temperature gradient in the deposited part, which is prone to thermal stress leading to cracks and delamination.

[0004] Porosity is one of the common defects in laser deposition additive manufacturing, which has a direct impact on the mechanical properties of components, especially the fatigue resistance, anisotropy, oxidation resistance and corrosion resistance of components.

[0005] As a self-fluxing alloy powder, nickel-based alloy powder has the advantages of good wettability, corrosion resistance, strong interface bonding with the matrix and moderate price. Its melting point and thermal expansion coefficient are consistent with the matrix material. Adding hard phase to nickel-based alloy powder can significantly improve the wear resistance, corrosion resistance and high temperature resistance of nickel-based alloy, and extend the service life of the workpiece. However, the hard phase will hinder the flow of liquid metal in the molten pool during laser deposition, and it is easy to cause defects such as pores in the coating. Some irregular hard phases will also produce stress concentration at the tip, causing cracks in the coating, which seriously reduces the performance of the additive parts.

[0006] By adding nanoscale hard phases to laser deposited powders, the formation of cracks and pores in laser deposition additive manufacturing can be effectively reduced, thereby increasing the mechanical properties and performance of the additive parts. Therefore, it is necessary to prepare a uniformly mixed nickel-based alloy powder. Currently, there are limited methods for preparing nickel-based alloy powders for additive manufacturing, mainly by ball milling nickel-based powders with hard phases to obtain nickel-based composite powders. However, since the particle size of the nanoscale hard phase is too small, agglomeration is prone to occur, and the hard phase is unevenly distributed in the obtained composite powder, resulting in uneven powder during the laser deposition additive process, which causes defects in the structure of the additive part, thereby reducing the overall performance of the additive part.

[0007] CN110952090B discloses a metal-based composite material perforating plug, which discloses an additive material with a certain amount of tungsten carbide added. However, there is no clear teaching on whether this material can overcome the unevenness and reduce defects, and the tungsten carbide particle size range used cannot achieve the corresponding technical effect. Summary of the invention

[0008] In view of the above problems, the present invention provides a method for preparing nickel-based alloy powder for additive manufacturing, which has the advantages of simple operation, short time and uniform mixing.

[0009] According to one aspect of the present invention, the present invention provides a method for preparing nickel-based alloy powder for additive manufacturing. The nickel-based alloy powder comprises 60-80 parts by weight of spherical Ni60 powder with a particle size of 70-120 microns and 40-20 parts by weight of tungsten carbide with a particle size of 20-100 nanometers.

[0010] The nickel-based alloy powder contains 20-40% by mass of nano-WC and has a particle size of 20-100 nanometers.

[0011] The nickel-based alloy powder contains 60-80% by mass of spherical Ni60 powder, and its mass composition is 0.5-1.1% of C, 0.0-5.0% of Fe, 15.0-20.0% of Cr, 3.0-4.0% of B, 0.06% of Si and the balance of Ni.

[0012] A method for preparing a nickel-based alloy powder for additive manufacturing comprises the following steps:

[0013] (1) Ni60 and nano-WC are used as raw materials, the proportion of the two raw materials is calculated according to the requirement of the amount of nano-WC in the final nickel-based alloy powder, and the two raw materials are mixed;

[0014] (2) subjecting the raw material mixture to magnetic stirring, using a magnetic stirring rotor as a stirring rod, using anhydrous ethanol as a stirring medium, a rotation speed of 600 r / min, and a stirring time of 1 hour;

[0015] (3) The mixed material after stirring in step (2) is placed in a drying oven for drying, heated to 120° C., and kept warm for 2-3 hours to finally obtain a nickel-based alloy powder with a pure physical phase.

[0016] Wherein, the method adopted in step (2) is magnetic stirring method.

[0017] The stirring medium used in step (2) is prepared by adding 100 g of the composite powder into 150 ml of anhydrous ethanol.

[0018] Compared with the prior art, the present invention has the following advantages:

[0019] 1. The present invention proposes to use a magnetic stirring method to prepare nickel-based alloy powder. During the magnetic stirring process, nano-WC adheres to the surface of Ni60 to form a core-shell structure, which greatly weakens the agglomeration of nano-WC.

[0020] 2. Among the alloy materials prepared by the present invention, Ni60 has the advantages of good wettability, corrosion resistance, firm interface bonding with the matrix and moderate price, and its melting point and thermal expansion coefficient are consistent with those of the matrix material.

[0021] 3. In the alloy material prepared by the present invention, nano-scale WC is easier to dissolve than micron-scale WC during the laser deposition additive manufacturing process, and the grains are refined and more uniform, which reduces the generation of pores and cracks in the additive parts and significantly improves the wear resistance and corrosion resistance of the additive parts.

[0022] 4. The mixing method used in the present invention is magnetic stirring, which is simpler and easier to operate than the composite powder mixing method. Nickel-based alloy powders of different mass proportions can be mixed according to the composite powder ratio required by the experiment.

[0023] 5. The nickel-based alloy powder for additive manufacturing prepared by the present invention has uniform distribution of component elements and low impurity content. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The following are scanning electron microscope images of Ni60 powder and nano-WC; (a) is Ni60 powder magnified 100 times, (b) is Ni60 powder magnified 500 times, and (c) is nano-WC powder.

[0025] Figure 2 The figures are scanning electron microscope images of the prepared nickel-based alloy powder for additive manufacturing; (a) is a scanning electron microscope image of the nickel-based alloy powder magnified 100 times, and (b) is a scanning electron microscope image of the nickel-based alloy powder magnified 500 times.

[0026] Figure 3 It is a macroscopic morphology diagram: A is Ni60; B is Example 4, and C is Example 5.

[0027] Figure 4 It is a penetration test diagram: A is Ni60; B is Example 4, and C is Example 5. DETAILED DESCRIPTION

[0028] The present invention is further explained in the following examples, but the present invention is not limited to the following examples. The following examples are all based on the preparation of nickel-based alloy powder for additive manufacturing as an example.

[0029] Example 1

[0030] Ni60 (morphology as Figure 1 a) and nano-WC (morphology such as Figure 1 c) as raw materials, and the final prepared Ni60 and nano WC are mixed in a mass ratio of 6:4, and the raw material mixture is magnetically stirred, with the magnetic stirring rotor as the stirring rod, anhydrous ethanol as the stirring medium, the speed is 600r / min, and the stirring time is 1 hour. The stirred mixture is placed in a drying oven for drying, heated to 120°C, and kept warm for 2-3 hours, and finally a phase-pure nickel-based alloy powder is obtained.

[0031] Example 2

[0032] Ni60 (morphology as Figure 1 a) and nano-WC (morphology such as Figure 1 c) as raw materials, and the final prepared Ni60 and nano WC are mixed in a mass ratio of 7:3, and the raw material mixture is magnetically stirred, with the magnetic stirring rotor as the stirring rod, anhydrous ethanol as the stirring medium, the speed is 600r / min, and the stirring time is 1 hour. The stirred mixture is placed in a drying oven for drying, heated to 120°C, and kept warm for 2-3 hours, and finally a phase-pure nickel-based alloy powder is obtained.

[0033] Example 3

[0034] Ni60 (morphology as Figure 1 a) and nano-WC (morphology such as Figure 1 c) as raw materials, and the final prepared Ni60 and nano WC are mixed in a mass ratio of 8:2, and the raw material mixture is magnetically stirred, with the magnetic stirring rotor as the stirring rod, anhydrous ethanol as the stirring medium, the speed is 600r / min, and the stirring time is 1 hour. The stirred mixture is placed in a drying oven for drying, heated to 120°C, and kept warm for 2-3 hours, and finally a phase-pure nickel-based alloy powder is obtained.

[0035] Example 4

[0036] The Ni60 powder particle size is 70 microns Ni60 and 20 nanometers WC (morphology as Figure 1c) as raw materials, and the final prepared Ni60 and nano WC are mixed in a mass ratio of 7:3. The Ni60 powder is composed of 0.5-1.1% C, 0.0-5.0% Fe, 15.0-20.0% Cr, 3.0-4.0% B, 0.06% Si and the balance Ni. The raw material mixture is magnetically stirred and mixed, with a magnetic stirring rotor as a stirring rod, anhydrous ethanol as a stirring medium, 100 grams of composite powder is added to 150 ml of anhydrous ethanol for proportioning, the speed is 600r / min, and the stirring time is 1 hour. The stirred mixture is placed in a drying oven for drying, heated to 120°C, and kept warm for 2-3 hours to finally obtain a nickel-based alloy powder with pure physical phase.

[0037] Example 5

[0038] The Ni60 powder particle size is 120 microns Ni60 and 40 nanometers WC (morphology as Figure 1 c) as raw materials, and the final prepared Ni60 and nano WC are mixed in a mass ratio of 7:3. The Ni60 powder is composed of 0.5-1.1% C, 0.0-5.0% Fe, 15.0-20.0% Cr, 3.0-4.0% B, 0.06% Si and the balance Ni. The raw material mixture is magnetically stirred and mixed, with a magnetic stirring rotor as a stirring rod, anhydrous ethanol as a stirring medium, 100 grams of composite powder is added to 150 ml of anhydrous ethanol for proportioning, the speed is 600r / min, and the stirring time is 1 hour. The stirred mixture is placed in a drying oven for drying, heated to 120°C, and kept warm for 2-3 hours to finally obtain a nickel-based alloy powder with pure physical phase.

[0039] Comparative Example 1

[0040] The Ni60 powder particle size is 150 microns Ni60 and 20 nanometers WC (morphology as Figure 1 c) as raw materials, and the final prepared Ni60 and nano WC are mixed in a mass ratio of 7:3. The Ni60 powder is composed of 0.5-1.1% C, 0.0-5.0% Fe, 15.0-20.0% Cr, 3.0-4.0% B, 0.06% Si and the balance Ni. The raw material mixture is magnetically stirred and mixed, with a magnetic stirring rotor as a stirring rod, anhydrous ethanol as a stirring medium, 100 grams of composite powder is added to 150 ml of anhydrous ethanol for proportioning, the speed is 600r / min, and the stirring time is 1 hour. The stirred mixture is placed in a drying oven for drying, heated to 120°C, and kept warm for 2-3 hours to finally obtain a nickel-based alloy powder with pure physical phase.

[0041] Comparative Example 2

[0042] The Ni60 powder with a particle size of 120 microns and 50 nanometers of WC are used as raw materials, and the final Ni60 and nanometer WC are mixed in a mass ratio of 7:3. The Ni60 powder has a mass composition of 0.5-1.1% C, 0.0-5.0% Fe, 15.0-20.0% Cr, 3.0-4.0% B, 0.06% Si and the remainder Ni. The raw material mixture is magnetically stirred and mixed, with a magnetic stirring rotor as a stirring rod, anhydrous ethanol as a stirring medium, 100 grams of composite powder is added to 150 milliliters of anhydrous ethanol for proportioning, the speed is 600r / min, and the stirring time is 1 hour. The stirred mixture is placed in a drying oven for drying, heated to 120°C, and kept warm for 2-3 hours, and finally a nickel-based alloy powder with pure physical phase is obtained.

[0043] Comparative Example 3

[0044] The Ni60 powder with a particle size of 120 microns and 10 nanometers of WC are used as raw materials, and the final Ni60 and nanometer WC are mixed in a mass ratio of 7:3. The Ni60 powder has a mass composition of 0.5-1.1% C, 0.0-5.0% Fe, 15.0-20.0% Cr, 3.0-4.0% B, 0.06% Si and the remainder Ni. The raw material mixture is magnetically stirred and mixed, with a magnetic stirring rotor as a stirring rod, anhydrous ethanol as a stirring medium, 100 grams of composite powder is added to 150 milliliters of anhydrous ethanol for proportioning, the speed is 600r / min, and the stirring time is 1 hour. The stirred mixture is placed in a drying oven for drying, heated to 120°C, and kept warm for 2-3 hours, and finally a nickel-based alloy powder with pure physical phase is obtained.

[0045] Experimental data analysis

[0046] Comparing Examples 4 and 5, as well as Comparative Examples 1, 2, and 3, it can be found that a certain degree of agglomeration occurred in Comparative Example 3, and the uniformity of the nickel-based alloy powder was poor, mainly because tungsten carbide of about 10 nanometers was used. It can be concluded that if finer nano-tungsten carbide is used in the compounding system, the hard phase distribution is uneven, resulting in uneven powder during the laser deposition additive process, which causes defects in the structure of the additive part, and cannot significantly improve the performance, and will also increase the manufacturing cost of the material. Comparative Example 1 used 150 microns of Ni60. Experiments found that it did not significantly change the uniformity and fluidity of the powder during the laser deposition additive process, but found that the fluidity of Ni60 itself was slightly affected, and the overall performance was not as good as the solution of the present invention. Ni60 should also be controlled within a reasonable range. Comparative Example 2 used 50 nanometers of WC as a raw material, which exceeded the particle size range selected by the present invention. It was found that it would affect the flow of Ni60, and tiny cracks appeared on the surface of the additive.

[0047] The difference between Examples 4 and 5 is that the composite system of Example 4 uses a more reasonable particle size, that is, Example 5 uses 120 micron Ni60 and 40 nanometer WC, while Example 4 uses 70 micron Ni60 and 20 nanometer WC. Comparative experiments show that Example 4 has the best performance. It is easier to dissolve than micron-level WC in the laser deposition additive manufacturing process, and the grains are refined most evenly, which reduces the generation of pores and cracks in the additive parts, and significantly improves the wear resistance and corrosion resistance of the additive parts.

[0048] Using the nickel-based alloy powders of Examples 4 and 5, as well as powder without tungsten carbide added, laser cladding technology was used to conduct experiments on the surface of 17-4PH precipitation-strengthened stainless steel. The laser cladding experiments found that compared with the cladding layer prepared with Ni60+30% WC powder, the cladding layer using Ni60+30% nano WC had a more obvious metallic luster, better molding, and no obvious cracks were found.

[0049] powder Power(W) Powder feeding speed (g / min) Scanning speed (mm / s) A Ni60 2000 25 2 B. Example 4 2000 25 2 C Example 5 2000 25 2

[0050] Each cladding layer was subjected to penetrant testing. First, a cleaning agent was sprayed onto the surface of the cladding layer to clean the oil stains on the surface, and then a red penetrant was sprayed. After waiting for 5-10 minutes, the penetrant on the surface of the cladding layer was cleaned with a cleaning agent, and after wiping it with a paper towel, a white developer was evenly sprayed. The flaw detection found that the cladding layer with Ni60 added contained a large number of cracks, and the cracks ran through the entire cladding layer. No large cracks were found on the cladding layer using the powder of Example 5, and no obvious cracks were found in the material of the powder of Example 4.

[0051] The laser cladding test revealed that, compared with the cladding layer prepared with Ni60+30% WC powder in Example 5, the cladding layer using Ni60+30% nano WC in Example 4 had a more obvious metallic luster, was better formed, and no obvious cracks were found.

[0052] The above embodiments are only preferred implementations of the technical solutions of the present invention, and the specific protection scope shall be subject to the records in the claims.

Claims

1. A method for preparing nickel-based alloy powder for additive manufacturing, characterized in that: The following steps are involved: (1) Ni60 powder and nano-tungsten carbide are used as raw materials, the proportion of the above two raw materials is calculated according to the requirement of the content of nano-tungsten carbide in the final nickel-based alloy powder, and the two raw materials are mixed; the Ni60 powder is composed of the following components by mass percentage: 0.5-1.1% C, 0.0-5.0% Fe, 15.0-20.0% Cr, 3.0-4.0% B, 0.06% Si and the balance Ni; the Ni60 powder is a spherical powder with a particle size of 70 microns, the particle size of the nano tungsten carbide is 20 nanometers; and the mass ratio of the Ni60 to the nano WC is 7:3; (2) The raw material mixture is subjected to magnetic stirring, with the magnetic stirring rotor as the stirring rod, anhydrous ethanol as the stirring medium, the rotation speed is 600 r / min, and the stirring time is 1 hour to obtain a composite powder; the amount of anhydrous ethanol and the raw material mixture is 150 ml of anhydrous ethanol plus 100 g of the composite powder; (3) The mixed material after stirring in step (2) is placed in a drying oven for drying, heated to 120° C., and kept warm for 2-3 hours to finally obtain a nickel-based alloy powder with a pure phase.

Citation Information

Patent Citations

  • A perforated mandrel made of metal matrix composite material

    CN110952090B

  • Composite powder for laser cladding and preparation method thereof

    CN110846537A